PENGARUH MODEL PJBL BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR - Nemu Yayuk Cipta Mudra; Imas Srinana Wardani (JS (JURNAL SEKOLAH), 2025)
Abstract: This research is is based on the issue of students' low critical thinking skills, especially in science education. The aim of this study is to determine whether the PjBL learning model based on education for sustainable development can affect students' critical thinking skills. The method used in this study is a quasi-experimental design with a non-equivalent control group type, with a research population of 56 students. The sample consisted of 23 class IV A students (experimental group) and 23 class IV B students (control group). This research sample was selected using a purposive sampling technique. The data collection method used is a test. Based on data analysis, the PjBL model based on education for sustainable development has a significant influence on the critical thinking abilities of fourth grade elementary school students. This is based on the results of the independent t test showing a sig value of 0.000 indicating a sig value <0.05 which can be concluded that  is rejected and  is accepted. Thus, the PjBL model based on education for sustainable development has an effect on students' critical thinking abilities. Keyword: PjBL; education for sustainable development; critical thinking Abstrak: Penelitian ini didasari oleh permasalahan rendahnya kemampuan berpikir kritis siswa, terutama dalam pembelajaran IPA. Tujuan dari penelitian ini adalah untuk mengetahui apakah model pembelajaran PjBL yang berbasis education for sustainable development dapat mempengaruhi kemampuan berpikir kritis siswa. Metode yang digunakan dalam penelitian ini adalah desain quasi eksperimental dengan jenis non equivalent control group, dengan populasi penelitian sebanyak 56 siswa. Sampelnya terdiri atas 23 siswa kelas IV A (kelompok eksperimen) dan 23 siswa kelas IV B (kelompok kontrol). Teknik purposive sampling digunakan pada pengambilan sampel. Metode pengumpulan data yang digunakan adalah tes. Berdasarkan penganalisisan data, model pembelajaran PjBL berbasis education for sustainable development memberikan pengaruh signifikan terhadap kemampuan berpikir kritis siswa kelas IV SD. Hal tersebut didasarkan pada hasil uji t independent menunjukkan nilai sig sebesar 0,000 menujukkan nilai sig < 0,05 yang dapat disimpulkan  ditolak dan  diterima. Dengan demikian, model pembelajaran PjBL berbasis education for sustainable development berpengaruh terhadap kemampuan berpikir kritis siswa.  Kata Kunci: PjBL; education for sustainable developmet; berpikir kritis